PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MAHASISWA UNTUK KULIAH DI STIE BENTARA PERSADA BATAM - Josepin Harianja, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This research has been completed to decide the influence of service quality, staffs performance for the satisfaction of students in STIE Bentara Persada Batam. The technique of collecting data of this research is by using questionaire, library research and interview. This research method uses quantitative research method. The numbers of population in this research are 100 respondents; they are the students of STIE Bentara Persada Batam that's still active in even semester of year 2018/2019. The samples method in this research are 100. Based on the result of this research, shows that every variable gives the positive and significant result for the customers satisfaction of STIE Bentara Persada Batam; with ttest (5,691)>ttable (1,984) and significance 0,00<0,05. Based on the test F, the quality and performance of staff gives the positive and significant influence for the satisfaction of customers; by result Ftest (49,563)>Ftable (3,090). From the result of hipothesis evidence, we can conclude that the service and performance quality, individually and team, has the satisfaction for students to study in STIE Bentara Persada Batam